A SHARP EDGE FORK SHAPED DUAL BAND MICROP STRIP PATCH ANTENNA FOR UWB APPLICATIONS (International Journal of Food and Nutritional Sciences, 2022)
The Dual Band Micro Strip Antenna was presented in this paper. The present work deals with the design of a sharp-edged fork shaped Micro strip patch antenna that can be used for various applications. The proposed antenna resonates at a double band of 4.1GHz and 7.7GHz giving an impedance bandwidth of 18.83%. The dual band Micro strip antenna is excited by a micro strip fed line.